Recurrent Burkholderia Infection in Patients with Chronic Granulomatous Disease: 11-Year Experience at a Large Referral Center - Greenberg, David E. (2009)
The epidemiology of Burkholderia infection in persons with chronic granulomatous disease is poorly understood. We used species-specific polymerase chain reaction–based assays and genotyping analyses to identify 32 strains representing 9 Burkholderia species among 50 isolates recovered from 18 patients with chronic granulomatous disease. We found that recurrent pulmonary infection with distinct Burkholderia strains is common in chronic granulomatous disease.